Remote Audit Compared to Onsite Audit and the Capabilities Required in the View of Internal Auditor Practices - Ria Ria (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The COVID-19 pandemic has made the business model change even faster. One of the things that must be adjusted is the organization that is engaged in auditing, especially internal audit. If in the past, the audit process was carried out with on-site visits, now it can be done with a new process called remotes audits. therefore, this requires new competence in conducting audits, especially how to conduct remote audits, but can still produce audit reports of the same quality as the previous reports. In practice, there are some similarities and differences in conducting remote audits compared to onsite audits. This paper will discuss the internal auditor's views regarding the similarities and differences between the remote audits and onsite audits processes from the view of auditors practitioners and what capabilities the auditor needs to deepen so that the remote audits process can run well. this study uses an explorative descriptive method involving 20 internal auditors as respondents, who were asked for their opinion in October 2022. The results of the study indicates that there is no difference in the planning process and reporting process. The only difference is in fieldwork, where remote auditing is technically more difficult. In addition, auditors are expected to deepen their knowledge in the field of digital and communication technology.